2019
DOI: 10.1177/1078390319877444
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Functioning and Depression Scores Improve Significantly With Participation in Visiting Moms® Program

Abstract: BACKGROUND: Postpartum depression is the most common complication of childbearing can affect the entire family unit. Health professionals must strive to identify and develop effective, feasible solutions for women during this critical period. AIMS: To determine whether postpartum maternal functioning (as measured by the Barkin Index of Maternal Functioning) and depression symptoms (as measured by the Patient Health Questionnaire-9) were improved after participation in the Visiting Moms program. METHOD: Paired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…As mentioned, changes in all measures was in the direction that would indicate improved wellbeing (average score on function went up, average score on symptoms of stress, anxiety, and depression went down). For comparison, a Visiting Moms intervention (a preventative program providing social support to new birth parents) observed an average change of about 16 points on the BIMF over the course of about a year of visits [ 52 ]. The Visiting Moms study was conducted in a similar population to the current study (both were conducted in a sample endorsing minimal to mild depressive symptomatology), and the current study observed nearly a third of this change (average change of about five points on the BIMF) over the course of only six weeks.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, changes in all measures was in the direction that would indicate improved wellbeing (average score on function went up, average score on symptoms of stress, anxiety, and depression went down). For comparison, a Visiting Moms intervention (a preventative program providing social support to new birth parents) observed an average change of about 16 points on the BIMF over the course of about a year of visits [ 52 ]. The Visiting Moms study was conducted in a similar population to the current study (both were conducted in a sample endorsing minimal to mild depressive symptomatology), and the current study observed nearly a third of this change (average change of about five points on the BIMF) over the course of only six weeks.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Jewish Family and Children's Service does that via their Visiting Moms program, which systematically pairs volunteers with clients based on personality and preference. This program has seen impressive and statistically significant reductions in depressive symptoms 29 . By tailoring the program to the woman's needs, deficits are addressed which may also account for an almost 16‐point increase in maternal functioning, a construct meant to reflect daily postpartum functioning 30–32 …”
Section: Discussionmentioning
confidence: 99%
“…When patients are actively involved in medical decision-making, this has been shown to improve outcomes for patients with depression ( 36 ) whereas the assignment of an unacceptable depression treatment has been shown to lead to negative outcomes like poor treatment alliance and high rates of attrition ( 37 ). Several other non-pharmacological interventions for peripartum distress that centered the patient by taking an individualized approach and making efforts to lower barriers to support have also demonstrated a positive impact on mental health outcomes ( 38 , 39 ).…”
Section: Importance Of Patient-centered Care To Postpartum Mental Healthmentioning
confidence: 99%